1997
DOI: 10.1007/3-540-63465-7_212
|View full text |Cite
|
Sign up to set email alerts
|

Thermal monitoring on FPGAs using ring-oscillators

Abstract: Esta es la versión de autor de la comunicación de congreso publicada en: This is an author produced version of a paper published in: Abstract. In this paper, a temperature-to-frequency transducer suitable for thermal monitoring on FPGAs is presented. The dependence between delay and temperature is used to produce a frequency drift on a ring-oscillator. Different sensors have been constructed and characterized using XC4000 and XC3000 chips, obtaining typical sensibilities of 50 kHz per °C. In addition, the util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 2 publications
(2 reference statements)
0
21
0
Order By: Relevance
“…Boemo and López-Buedo in [21] showed that the frequency of a ring oscillator is a linear function of power supply in the operation range. Hence, if the responses of a RO-PUF, generated with the same challenge at the minimum and the maximum voltages respectively, are equal, as the pair shown in Figure 4(a), the CRP is stable even when the supply voltage varies from the minimum voltage to the maximum voltage.…”
Section: B a Methods To Enroll Stable Crps Against Voltage Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Boemo and López-Buedo in [21] showed that the frequency of a ring oscillator is a linear function of power supply in the operation range. Hence, if the responses of a RO-PUF, generated with the same challenge at the minimum and the maximum voltages respectively, are equal, as the pair shown in Figure 4(a), the CRP is stable even when the supply voltage varies from the minimum voltage to the maximum voltage.…”
Section: B a Methods To Enroll Stable Crps Against Voltage Variationmentioning
confidence: 99%
“…How frequency of a ring oscillator varies with temperature and voltage is studied by Boemo and López-Buedo in [21]. They have shown that the frequency of a ring oscillator is a linear function of both the temperature in the normal range of operation, and the power supply in the operation range.…”
Section: A Scheme To Enroll Stable Crpsmentioning
confidence: 98%
“…We performed several experiments to verify the ideas [5]- [7]. The last one was to measure the thermal behavior of two 32-bit PLASMA microprocessors, compatible with MIPS-I [8], whose VHDL code was obtained from the opencores.org initiative.…”
Section: Testing a Microprocessor Twin-corementioning
confidence: 99%
“…The utilization of ring-oscillators as thermal sensors on FPGAs was first explored in [9]. The advantages of ringoscillators in a reprogrammable logic framework are multiple: it allows the designer the detection of hot spots or signal contentions [10], as well as the possibility of inserting an array of sensors using dynamic configuration to get a real-time thermal map of the FPGA [11].…”
Section: Introductionmentioning
confidence: 99%